2011
DOI: 10.1007/s11060-011-0630-5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary use of differential scanning calorimetry of cerebrospinal fluid for the diagnosis of glioblastoma multiforme

Abstract: Thermal stability signatures of complex molecule interaction in biological fluids can be measured using a new approach called differential scanning calorimetry (DSC). The thermal stability of plasma proteome has been described previously as a method of producing a disease-specific "signature," termed thermogram, in several neoplastic and autoimmune diseases. We describe the preliminary use of DSC performed on cerebrospinal fluid (CSF) as a diagnostic tool for the identification of patients with glioblastoma mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…To-date, the thermograms for each disease are markedly different from one other and this leads to our current focus in developing this assay as a clinical diagnostic tool for early disease screening. The general applicability of DSC analysis with potential for clinical diagnostics is further underlined by reports from other investigators indicating promising preliminary results for DSC analysis of a number of diseases [2530]. Here we report the application of DSC to examine the plasma proteome of selected samples obtained during the 1 st Joslin Study of the Natural History of Microalbuminuria in Type 1 Diabetes [31].…”
Section: Introductionmentioning
confidence: 92%
“…To-date, the thermograms for each disease are markedly different from one other and this leads to our current focus in developing this assay as a clinical diagnostic tool for early disease screening. The general applicability of DSC analysis with potential for clinical diagnostics is further underlined by reports from other investigators indicating promising preliminary results for DSC analysis of a number of diseases [2530]. Here we report the application of DSC to examine the plasma proteome of selected samples obtained during the 1 st Joslin Study of the Natural History of Microalbuminuria in Type 1 Diabetes [31].…”
Section: Introductionmentioning
confidence: 92%
“…Under given solution conditions, a thermogram provides a unique signature for a given protein reflecting specific structural motifs and molecular forces. It has recently been shown that DSC can be applied to the analysis of blood plasma to provide an indication of an individual’s clinical status [15], [16], [17], [18], [19], [20], [21], [22], [23], [24]. The thermogram of plasma from healthy individuals reflected the weighted sum of the denaturation profiles of the most abundant plasma proteins; however, thermograms from individuals with various conditions or diseases were significantly changed [15], [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In a recent study performed at the University of Utah, DSC was applied to CSF samples obtained from 9 patients with GBM, as well as multiple patients with other tumoral and nontumoral conditions. 4 The thermograms were compared to each other in preliminary fashion to assess for transitions and broadness of peaks. CSF was chosen instead of serum because of being in closer contact to the central nervous system than the serum, potentiating higher sensitivity in the search for GBM-specific proteins.…”
Section: Differential Scanning Calorimetry Applied To Cerebrospinal Fmentioning
confidence: 99%